The preferred futures of a human-centric society : A case of developing a life-event-based visioning approach - Villman, Tero (My University, 2021)
The field of futures studies is affected by a lack of consensus in many regards. From the terminology and methodologies to the overall definition of futures studies and its purposes. However, the considerations regarding alternative futures and an orientation towards the pursuit of futures better than the present have continued to be foundational to the field. Furthermore, visions and visioning are considered key concepts of futures studies, and visioning one of the methods unique to the field. Still, they share the same issues as many other concepts and methods in futures studies: multiple meanings, dissimilar and sometimes contradictory definitions, characteristics and principles, and an array of techniques and methods have surfaced. To develop as a field, increasing understanding regarding visions and visioning, more rigorous visioning methodology and visions of higher quality are called for. For that purpose, this research explores the various interpretations for visions and visioning as concepts in futures research and foresight through multiple lenses. The research discusses definitions, types, forms, qualities, processes and functionings, and as result proposes definitions for both vision and visioning. In addition, the research studies the conceptual frame, Futures Map, to examine the possibilities of applying it for understanding and visualizing a dynamic futures landscape and the role of visions in them. The research suggests to view the creation of a vision and actions towards it as a journey on a dynamic Futures Map: developing a shared understanding of the futures landscape and the preferred destinations, committing to a path leading to their direction, constantly gaining awareness of and adapting to both internal and external change, and revising the destination, direction and actions. Furthermore, this practically-oriented research describes the process implemented in the national artificial intelligence program AuroraAI to develop and pilot a participatory approach for visioning the preferred futures of a human-centric society through the lenses of life-events and situations in life. The developed approach was piloted with a single life-event, and as result of the visioning process the preferred futures of human-centric society in Finland 2040 from the perspective of 13–16-year-olds in basic education were constructed with participants representing the age group and their stakeholders. Both the further examination of the Futures Map and the utilization of life-event-based thinking in the visioning approach may be considered new research contributions.

Yhteisymmärryksen puute vaikuttaa tulevaisuudentutkimukseen monessa suhteessa. Käsitteistä ja metodologioista tulevaisuudentutkimuksen määritelmään ja tavoitteisiin. Silti tulevaisuuksien vaihtoehtoisuutta koskevat näkökulmat ja suuntautuminen nykyisyyttä parempien tulevaisuuksien tavoitteluun ovat pysyneet keskeisinä. Lisäksi visioita ja visiointia pidetään tulevaisuudentutkimusten keskeisinä konsepteina ja visiointia yhtenä sen ainutlaatuisista menetelmistä. Siitä huolimatta niitä koskee samat kysymykset kuin monia tulevaisuudentutkimuksen käsitteitä ja menetelmiä: on useita merkityksiä, erilaisia ja ristiriitaisiakin määritelmiä, ominaisuuksia ja periaatteita, sekä on esitetty lukuisa joukko erilaisia menetelmiä ja tekniikoita. Tulevaisuudentutkimuksella on kehittyäkseen tarve kasvattaa visioita ja visiointia koskevaa ymmärrystä sekä tuottaa korkealaatuisia visioita ja perusteellisia visiointiprosesseja. Tähän tarkoitukseen tässä tutkimuksessa tutkitaan visioita ja visiointia tulevaisuudentutkimuksessa ja ennakoinnissa useiden linssien kautta. Tutkimuksessa käsitellään määritelmiä, tyyppejä, muotoja, ominaisuuksia, prosesseja ja toimintoja, ja niiden perusteella esitetään määritelmät visiolle ja visioinnille. Lisäksi tutkimuksessa tarkastellaan käsitteellistä kehystä, tulevaisuuksien karttaa, tarkoituksena tunnistaa mahdollisuuksia soveltaa sitä dynaamisen tulevaisuuksien maiseman hahmottamiseen ja visualisointiin sekä kuvata visioiden roolia niissä. Tutkimus esittää, että vision luontia ja sen suuntaan johtavia toimia voidaan kuvata matkana dynaamisella tulevaisuuksien kartalla: kehitetään yhteinen näkemys tulevaisuuksien maisemasta ja toivottavista määränpäistä, sitoudutaan toivottuun suuntaan johtavaan polkuun, jatkuvasti rakennetaan ymmärrystä ja mukaudutaan sisäisiin sekä ulkoisiin muutoksiin, ja uudelleenarvioidaan sekä päivitetään toivottua määränpäätä, suuntaa ja tarvittavia toimia. Lisäksi tämä käytännöllisesti suuntautunut tutkimus kuvaa kansallisessa tekoälyohjelmassa AuroraAI:ssa toteutettua prosessia, jossa kehitettiin ja pilotoitiin osallistavaa lähestymistapaa ihmiskeskeisen yhteiskunnan toivottavien tulevaisuuksien visioimiseksi elämän eri tilanteiden ja tapahtumien näkökulmasta. Kehitettyä lähestymistapaa pilotoitiin yhdellä elämäntapahtumalla, ja visiointiprosessin tuloksena rakentui ihmiskeskeisen yhteiskunnan toivottavat tulevaisuuskuvat Suomessa 2040 yläkouluikäisten näkökulmasta kyseisen ikäryhmän edustajien ja heidän sidosryhmiensä kanssa. Sekä tulevaisuuksien kartan tarkastelua, että elämäntapahtuma-ajattelun hyödyntämistä visioinnissa voidaan pitää uutena tutkimustyönä.
Keywords: vision, visioning, images of the future, preferred futures, futures map, human-centric, life-event, futures studies